Geology and geochemistry of the Frontino-Morrogacho Gold District (2018)
"This work presents a geological and geochemical characterization of gold and silver mineralizations located in the Frontino-Morrogacho mining district, located in the west of the Antioquia province."-- Tomado del Formato de Documento de Grado